Statement from Alliance Quebec on the Ontario Government's Failure to Grant the New Ottawa Megacity Official BIlingual Status - Alliance Quebec (AQ) (1999)

"Many Sections of the Charter of the French Language Violate the Constitutional Rights of Quebecers:" AQ President William Johnson - Alliance Quebec (AQ) (1999)

Language Learning in the English Schools of Quebec : A Biliteracy Imperative - Advisory Board on English Education (1995)
The school board reorganization, which sooner or later is bound to come about, will force major adjustments on the delivery of English education. The forming of a true English school network through the fusion of the existing Catholic and Protestant structures will provide both an opportunity to strengthen and rationalize the English school system and a challenge to get it right. By getting it right is meant finding an educational mission to which all the constituencies of the English-speaking community and the schools which serve it can respond.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1983)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1981)
issued: March, 1981/April, 1981 Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1981)
issued: January, 1981/February, 1981 Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1980)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1978)
issued: February, 1978/March, 1978 Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1977)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1976)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1976)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1975)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1974)
Number of pages: 17

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1974)
issued: March, 1974/April, 1974 Number of pages: 16